2020
DOI: 10.1186/s40170-020-00215-8
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine uptake and utilization of human mesenchymal glioblastoma in orthotopic mouse model

Abstract: Background: Glioblastoma (GBM) are highly heterogeneous on the cellular and molecular basis. It has been proposed that glutamine metabolism of primary cells established from human tumors discriminates aggressive mesenchymal GBM subtype to other subtypes. Methods: To study glutamine metabolism in vivo, we used a human orthotopic mouse model for GBM. Tumors evolving from the implanted primary GBM cells expressing different molecular signatures were analyzed using mass spectrometry for their metabolite pools and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Glutamine catabolism independence has also been reported in other in vivo tumor models [39]. In the context of glioblastoma, some studies have maintained that pyruvate-derived carbons dominate those coming from glutamine in the TCA cycle [39,40], while another recent study showed that the origin of the glioblastoma cells influences their preference of anaplerotic substrate [45]. Overall, dependence on glutamine oxidation appears to be heterogenous, and dictated by underlying genetics [43,46], tissue origin [46], and tumor microenvironment [44,47], and glutamine auxotrophy may not be a universal characteristic of cancer cells in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Glutamine catabolism independence has also been reported in other in vivo tumor models [39]. In the context of glioblastoma, some studies have maintained that pyruvate-derived carbons dominate those coming from glutamine in the TCA cycle [39,40], while another recent study showed that the origin of the glioblastoma cells influences their preference of anaplerotic substrate [45]. Overall, dependence on glutamine oxidation appears to be heterogenous, and dictated by underlying genetics [43,46], tissue origin [46], and tumor microenvironment [44,47], and glutamine auxotrophy may not be a universal characteristic of cancer cells in vivo.…”
Section: Discussionmentioning
confidence: 80%
“…Glutamine catabolism independence has also been reported in in vivo tumor models (38). In the context of glioblastoma, some studies have maintained that pyruvate-derived carbons dominate those coming from glutamine in the TCA cycle (38,39), while another recent study showed that the origin of the glioblastoma cells influences their preference of anaplerotic substrate (43). Overall, dependence on glutamine oxidation appears to be heterogenous, and dictated by underlying genetics (16,44), tissue origin (44), and tumor microenvironment (42,45) and glutamine auxotrophy may not be a universal characteristic of cancer cells in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, the group of patient-derived GSCs that uptake high glutamine levels, transcriptomically classifies as the GBM mesenchymal subtype, while the glucose-dependent group does not ( Oizel et al, 2017 ). Not surprisingly, tumours generated by mesenchymal GSCs show increased glutamine uptake and conversion to glutamate when compared to non-mesenchymal GSCs ( Oizel et al, 2020 ). In the same study, it was shown that the non-mesenchymal GSCs (which belong to the proneural and classical subtypes) express high levels of GS ( Oizel et al, 2020 ).…”
Section: Glioblastomamentioning
confidence: 99%
“…Not surprisingly, tumours generated by mesenchymal GSCs show increased glutamine uptake and conversion to glutamate when compared to non-mesenchymal GSCs ( Oizel et al, 2020 ). In the same study, it was shown that the non-mesenchymal GSCs (which belong to the proneural and classical subtypes) express high levels of GS ( Oizel et al, 2020 ). These studies seem to contradict the work mentioned earlier by Tardito et al (2015) and Marin-Valencia et al (2012) , in which the authors described that the stem-like population does not depend on glutamine.…”
Section: Glioblastomamentioning
confidence: 99%